Bistable prestressed spring steel grippers for aerial perching and grasping - Jones, Bryce, author; Zhao, Jianguo, advisor; Ciarcia, Marco, committee member; Simske, Steve, committee member (Colorado State University. Libraries, 2024)
Quadcopter drones are popular in both the consumer and commercial markets, with a wide range of uses and applications, including inspections, research, natural disaster response, and filming and photography. These uses and applications are currently limited, however, by the limited battery power and range of current drones. Aerial perching can extend the useful flight time of a drone by allowing for passive perching in a location for a desired amount of time. Compliant bistable mechanisms are well-suited for this application because of their adaptability in a wide range of environments while utilizing bistability to reduce energy consumption and complexity. Current research into aerial perching with compliant mechanisms is limited to heavy, rigid grippers with limited applications in a wide variety of environments and grippers with complicated pneumatic controls. In this thesis, we propose a novel solution to this gap in research through the use of prestressed spring steel bands (PSSB) to create compliant bistable grippers for aerial perching and grasping. We investigate multiple different PSSB configurations. We first investigate two single PSSB gripper designs, a single band gripper with a cable driven opening system, then an improved silicone encased single PSSB gripper design. The first single band gripper is experimentally tested to determine the triggering force, effect of offset on triggering force, effect of spring pretension on triggering force, opening force, grasping force, and activation time. This design had some issues with opening reliably and tangling. The improved silicone encased gripper is experimentally tested for triggering force, the effect of varying contact points and angles, activation time, reduction of triggering force with springs, and actual flight tests on a drone done in partnership with IIIT Hyderabad. The single band gripper designs can grasp a variety of objects, especially cylindrical ones, but are limited in grasping spherical and heavier objects, and vertical grasping. We then design a cross-shaped gripper based on the silicone encased PSSB gripper. This gripper is experimentally tested in the same manner as the silicone encased single band gripper and performs well in grasping spherical objects and vertical grasping. It does, however, struggle to grasp longer cylindrical objects. These gripper designs have a fixed triggering force based on the design that limited the applications for drone applications with high acceleration causing inadvertent activation, as well as for grasping lightweight objects. Being able to actively control the triggering force of the grippers would give the ability to tune the gripper for ideal performance in a wide range of applications. To actively tune the triggering force, we investigate the use of on the fly tuning with Nitinol Shape Memory Alloy springs. We first attempted closed-loop control by using a PID controller to control the resistance of the springs. Then we used an open loop control method where constant voltage is applied to the springs that allows for precise tuning of the triggering force to a set range for the desired application, and experimentally verify the reduction in triggering force and show the application of on the fly triggering force tuning.